Case Report: Type 2 Diabetes Mellitus - Shofi Hesfianto (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2018)
.......A patient who was first diagnosed with a chronic disease often does not fully understand the meaning or significanceof the chronic disease with which his/ her body suffers, against the risk of future complications if the disease is not well-controlled. On the other hand, in this reported case, the patient’s expectation was that her chronic disease, the T2DM, can be cured. Therefore, a shared understanding between health care providers and patient is likely the key to commencing the course of managing any chronic disease in a patient effectively.......